Analisis Antrean SPBU dengan Model M/M/c dan Simulasi Arena untuk Optimalisasi (Studi Kasus: SPBU NOMOR 14.201.125, MEDAN) - simarmata, roberta; Purba, Johana Sihol Marito; Alia Dwi Septia (LPPM-ITEBA, 2025)
This study analyzes the queuing system at the Gatot Subroto SPBU using the M/M/c model and Arena simulation to identify bottlenecks and optimize service. Arrival and service time data for motorcycles (Beta distribution) and cars (Weibull distribution) were modeled using Create, Hold, Decide, Process, and Dispose modules. M/M/c calculations (C = 2) showed high alignment for motorcycles (ρ = 0.0885, Wq = 0.02998 minutes) but less accuracy for cars (Wq = 0.1361 minutes) due to non-exponential distributions. Arena simulation revealed bottlenecks at POM 2 (Wq = 0.1202 minutes) and POM 4 (Wq = 0.3642 minutes) caused by uneven vehicle distribution, clustered arrivals, prolonged car service times, and FCFS discipline. A load balancing solution with 4 Decide modules and 10 replications increased pump utilization (POM 1: 60%, POM 2: 29%, POM 3: 61%, POM 4: 25%), reduced car service time (Ws decreased by 0.147 minutes), and lowered car queue length (Lq reduced by 0.0017), though motorcycle waiting time slightly increased (0.0255 minutes). Practical solutions include manual load balancing, pump flexibility, vehicle flow optimization, and supportive technology. The study demonstrates that load balancing effectively mitigates bottlenecks, but motorcycle service requires further improvement.